141k views
4 votes
4(2x3)-3x=5(x-2)+3 how do you do this?

User Ten Sleep
by
5.3k points

2 Answers

1 vote

First of all, we have to expand the brackets.

8 x 12 - 3x = 5x - 10 + 3

Then, we have to put all the x terms on one side. We do that by adding 3x to both sides to get rid of that -3x on the left.

8 x 12 = 8x - 10 + 3

Now we have to get x on its own, so if we do the numbers first to make it easier:

96 = 8x - 7

Now add seven to both sides: 103 = 8x

Then divide both sides by eight to find x. This leaves us with 12.875.

Hope I helped!

User Graymatter
by
5.6k points
5 votes
4(2×3)-3x=5(x-2)+3
24-3x=5x-7
8x=31
x=31/8
User CaseyB
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.